Too Much Future - Fiebeler, Carsten; Boehlke, Michael (Germany : Tossell, Egoli, 2007)
A documentary about punk in the GDR. The history of punk in the GDR is unique because the state and the ministry of state security acted in a disproportionate and massive way against people trying to break free. This led to a variety of biographies, full of dramatic turns, twists and incidents. “Too Much Future” focuses on two women and four men who lived in Berlin, Leipzig and Dresden. They talk about different designs for life, portray fractured biographies that have punk in common, and how they had to deal with being imprisoned by the GDR authorities. The film shows in an equally interesting way where the protagonists stand today: their lives, their professions, their political opinions and their punk.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films